2019
DOI: 10.3390/molecules24091783
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation and Docking Studies of 13-Epimeric 10-fluoro- and 10-Chloroestra-1,4-dien-3-ones as Potential Aromatase Inhibitors

Abstract: Fluorination of 13-epimeric estrones and their 17-deoxy counterparts was performed with Selectfluor as the reagent. In acetonitrile or trifluoroacetic acid (TFA), 10β-fluoroestra-1,4-dien-3-ones were formed exclusively. Mechanistic investigations suggest that fluorinations occurred via SET in acetonitrile, but another mechanism was operative in TFA. Simultaneous application of N-chlorosuccinimide (NCS) and Selectfluor in TFA led to a 1.3:1 mixture of 10β-fluoroestra-1,4-dien-3-one and 10β-chloroestra-1,4-dien-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Emodel was developed for pose selection and it uses the Glide score to rank poses against one another, where a low value indicates good protein-ligand binding affinity. [63,64] Therefore, the result from this study indicates that the hybrid compounds established more energetically favourable interactions than ursolic acid in the active site of the protein.…”
Section: Molecular Dockingmentioning
confidence: 71%
See 1 more Smart Citation
“…Emodel was developed for pose selection and it uses the Glide score to rank poses against one another, where a low value indicates good protein-ligand binding affinity. [63,64] Therefore, the result from this study indicates that the hybrid compounds established more energetically favourable interactions than ursolic acid in the active site of the protein.…”
Section: Molecular Dockingmentioning
confidence: 71%
“…The glide Emodel scores also showed a similar trend establishing the values −89.61, −68.56, −42.11 and −46.53 kcal/mol for the compounds 29, 34, ursolic acid and the co‐ligand, respectively ( Table 3). Emodel was developed for pose selection and it uses the Glide score to rank poses against one another, where a low value indicates good protein‐ligand binding affinity [63,64] . Therefore, the result from this study indicates that the hybrid compounds established more energetically favourable interactions than ursolic acid in the active site of the protein.…”
Section: Resultsmentioning
confidence: 92%
“…The tested compounds containing the 13β-Me group showed strong inhibitory effects with submicromolar and micromolar IC 50 values of 0.49, 5.0, and 2.4 µM. The reference compound in the study was androst-4-ene-3,17-dione with an IC 50 value of 0.22 µM [ 20 ].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%
“…When another radical scavenger, N-hydroxyphthalimide (NHPI) was tested, analysis of the crude product by HR-MS revealed the presence of the radical addition product 198. In 2019, Mernyak et al 167 reported the fluorination of 13β-estrone 199 using Selectfluor™ 25 in MeCN to obtain 10β-fluoroestra-1,3-den-3-one 200 in 95% yield (Scheme 19f). However, in the presence of TEMPO, the reaction was inhibited, with only 3% yield of fluorosteroid 200.…”
Section: Approaches Towards the Determination Of The Mechanism Of Fluorination By N-f Reagentsmentioning
confidence: 99%